Dose-dependent effects of atorvastatin in the hospitalisation period of myocardial infarction - O. L. Barbarash; O. V. Gruzdeva; O. E. Akbasheva; T. S. Fedorova; A. A. Silonova; E. I. Palicheva; E. G. Uchasova; V. N. Karetnikova; V. V. Kashtalap (Российский кардиологический журнал, 2013)
Aim. To compare the dynamic effects of atorvastatin doses 20 mg and 40 mg on lipid profile, insulin resistance markers, adipokines, prothrombotic, and proinflammatory status in myocardial infarction (MI) patients during the hospitalisation period. Material and methods. The study included 42 patients with ST segment elevation MI. Group 1 (n=21) received atorvastatin in the dose of 40 mg/day; Group 2 (n=21) was administered atorvastatin in the dose of 20 mg/day. At Day 1 and Day 12 after admission, the parameters of lipid profile (total cholesterol and its fractions, atherogenic index, free fatty acids, and triglycerides), carbohydrate metabolism (glucose, insulin, and C-peptide), insulin resistance (HOMA index), proinflammatory status (C-reactive protein and interleukin-6), prothrombotic status (plasminogen activator inhibitor-1), and adipokines (leptin, resistin, and adiponectin) were measured. Results. Dose-dependent effects of atorvastatin were already demonstrated in the early hospitalisation period: the 40 mg dose was more effective in terms of lipid profile improvement, while the 20 mg dose was more effective for insulin resistance correction. The increase in atorvastatin dose up to 40 mg was associated with a reduction in pancreatic insulin-producing function. The effects on inflammation and thrombogenesis markers were less dose-dependent. A lower dose of atorvastatin (20 mg) normalized adipokine levels (increased leptin concentration and increased protective effects of resistin), which could be regarded as a beneficial prognostic factor. Conclusion. The selection of atorvastatin dose in MI patients should take into account the adipokine status and the dynamics of biochemical markers of insulin resistance.